Modeling of Ethylene Polymerization Kinetics over Supported Chromium Oxide Catalysts - Choi, Kyu Yong; Tang, Shihua; Yoon, Won Jung (Macromolecular theory and simulations, 2004)
Silica supported chromium oxide catalysts have been used for many years to manufacture polyethylene and they still account for more than 50% of world production of high‐density polyethylene. Along with its commercial success, the catalytic mechanism and polymerization kinetics of silica supported chromium oxide catalysts have been the subject of intense research. However, there is a lack of modeling effort for the quantitative prediction of polymerization rate and polymer molecular weight properties. The chromium oxide catalyzed ethylene polymerization is often characterized by the presence of an induction period followed by a steady increase in polymerization rate. The molecular weight distribution is also quite broad. In this paper, a two‐site kinetic model is developed for the modeling of ethylene polymerization over supported chromium oxide catalyst. To model the induction period, it is proposed that divalent chromium sites are deactivated by catalyst poison and the reactivation of the deactivated chromium sites is slow and rate controlling. To model the molecular weight distribution broadening, each active chromium site is assumed to have different monomer chain transfer ability. The experimental data of semibatch liquid slurry polymerization of ethylene is compared with the model simulations and a quite satisfactory agreement has been obtained for the polymerization conditions employed. Polymerization rates at different reaction temperatures: symbols – data, lines – model simulations.